"Начальник Запорозьких церков" Володимир Сокальський. (Zaporizhzhia Historical Review, 2021)
The article is devoted to the biography of one of the well-known spiritual persons, which satisfied spiritual needs of Zaporizhyan Cossacks. The historiography and sources, which concern to the “chief of Zaporizhyan churches”, the archimandrite Vladimir Sokal'skiy, are analysed.